Consulting report – Mipaku - Perez Paredes, Elio David (2019)
MiPaku is a small, socially conscious fashion brand specializing in the design, manufacture, and sales of high-quality alpaca wool and cotton blended garments. The company is essentially an outgrowth of D’Peru textiles, which is an already established selfsustainable business that has been running since 2010. While Mipaku offers its products under its own brand name, D’Peru Textiles is a white-label label manufacturer of high-end alpaca wool and cotton blended garments. The company is based in Lima, Peru, and, at present, employs a total of 12 persons. Notably, Mipaku shares its production facilities, staff, warehousing, and ownership with D’Peru Textiles. Mipaku generates annual sales of less than US$10,000. Mipaku wants to grow yet is unsure of how to do so. Accordingly, the main problem(s) addressed in the consulting report concern market selection and modes of entry. In order to address the problem of market selection, an integrated market selection model is designed (based upon relevant literature) and employed to determine which markets Mipaku should pursue. Results from the model are complemented by qualitative research and identified that the United States, Germany, and the United Kingdom are the top markets for further pursuit. Following market selection, entrance strategies for each market are designed and organized into a Gantt chart. Moreover, the proposed implementation offers legal requirements, distribution channels, cost strategies, and a list of trade shows, boutiques, and other potential customers. Finally, it is analyzed the qualitative and quantitative outcomes that give the expected net present value and internal rate of return. To conclude, it is projected that if Mipaku implements the recommendations outlined in the consulting report, they will indeed accomplish their goal of increasing sales and growing their brand.